Modulation of cell migration by integrin-mediated cytoskeletal linkages and ligand-binding affinity (The Rockefeller University Press, 1996)
Integrin cell surface adhesion receptors play a central role in mediating cell migration. We have developed a model system consisting of CHO cells ectopically expressing the alpha IIb beta 3 integrin to study integrin affinity and cytoskeletal interactions during cell migration. The alpha IIb beta 3 integrins are suited for study of integrin receptors during cell migration because they are well characterized with respect to ligand binding, cytoskeletal interactions, and signal transduction, and mutants with altered receptor function are available. The alpha IIb beta 3 receptor specifically mediates migration of alpha IIb beta 3-transfected CHO cells. The migration of transfected CHO cells was studied on a fibrinogen substrate both by time lapse videomicroscopy and by random and haptotactic transwell assays. Haptotactic and random transwell assays measured distinct aspects of migration, with the random transwell assay correlating most closely with time lapse videomicroscopy. Mutations in the cytoplasmic domains that increase ligand affinity or activation of the alpha IIb beta 3 receptor into a high affinity state by the LIBS6 antibody decreased the migration rate. Likewise, mutations that increase cytoskeletal organization without affecting affinity also decreased the migration rate. In contrast, truncation of the beta chain, which alters cytoskeletal associations as assayed by absence of focal adhesions, decreased haptotactic migration while increasing random migration. These effects on the migration rate were partially compensated for by altering substrate concentration, demonstrating optimum substrate concentrations that supported maximal migration. For example, cells expressing integrins locked in the high affinity state showed maximal migration at lower substrate concentrations than cells expressing low affinity receptor. Together, these results implicate the strength of adhesion between cell and substrate, as modulated by receptor affinity, organization of adhesive complexes, and substrate concentration, as important regulators of cell migration rate. Further, we demonstrate a dominant effect of high affinity integrin in inhibiting migration regardless of the organization of adhesive complexes. These observations have potential implications for tumor metastasis and its therapy.